Cuypers, Copijn and the park of castle De Haar (Bulletin KNOB, 1996)
One of the subjects for research is the question to what extent Cuypers & Son also produced ideas on the lay-out of the park in country style. It is quite obvious from the accounts in the archives of De Haar that Henri Copijn executed both the Northern and the Southern Park. Here we also find confirmation for the legendary tales about full-grown trees taken to De Haar from far and near, in order to give the park a mature appearance as soon as possible. The part played by Cuypers and Copijn as landscape architects is still utterly obscure, in spite of all the attention that is being paid to their work nowadays. This is obviously a subject awaiting research, which will have to incorporate much more than just De Haar.The present dating, 1894, of the first large design of the gardens and the surrounding Northern and Southern Park of De Haar may be rather too early, but it was certainly made before 1900: the vegetable gardens are still indicated here on the site of the present Rose and Palm Garden. Nor has the Roman Garden been depicted yet. But the relocated village, which already existed in 1898, has. The plan even includes a large part of the estate to the west of the Rhine dyke in the lay-out in country style, belonging to the property nowadays, but still an agrarian area.Did Copijn provide the first sketches, which were subsequently worked out by Cuypers for presentation? Did Cuypers determine the sight axes (reaching as far as Zuilen!) and did he propose the construction in open spaces and planted islands, which Copijn worked out in further detail? These are all questions as yet unanswered, but in the meantime they do indicate what an important and fascinating creation the park and gardens of castle De Haar is, through the years effected in an ever-changing interaction between owner, architect and landscape architect.